2013
DOI: 10.1002/14651858.cd003707.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Partial liquid ventilation for preventing death and morbidity in adults with acute lung injury and acute respiratory distress syndrome

Abstract: No evidence supports the use of PLV in ALI or ARDS; some evidence suggests an increased risk of adverse events associated with its use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 45 publications
0
11
0
4
Order By: Relevance
“…) or partial liquid ventilation with perfluorocarbons to improve lung compliance, provide liquid positive PEEP, and improve ventilation‐perfusion matching (Galvin et al. ). Current recommendations from the National Institute of Health ARDS network for mechanical ventilation are a low V˙T (6 mL kg −1 ), initial use of PEEP 8–12 cmH 2 O, and using <100% oxygen.…”
Section: The Immune Response To Mechanical Ventilationmentioning
confidence: 99%
“…) or partial liquid ventilation with perfluorocarbons to improve lung compliance, provide liquid positive PEEP, and improve ventilation‐perfusion matching (Galvin et al. ). Current recommendations from the National Institute of Health ARDS network for mechanical ventilation are a low V˙T (6 mL kg −1 ), initial use of PEEP 8–12 cmH 2 O, and using <100% oxygen.…”
Section: The Immune Response To Mechanical Ventilationmentioning
confidence: 99%
“…Although lung protective ventilatory strategies have been widely applied, the mortality caused by ALI/ARDS is still high (Rubenfeld et al 2005;Galvin et al 2013). Therefore, a novel effective therapy is urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…However, a large-scale clinical trial reported a lack of benefit of PLV in adult patients with ARDS. It was even associated with increased risk of adverse events such as hypoxia, bradycardia, and respiratory acidosis (Galvin et al, 2013). These findings reduced interest in the use of PLV in ARDS patients.…”
Section: Introductionmentioning
confidence: 98%
“…TLV has also been shown to increase the mechanical recruitment of collapsed alveoli and the ventilation/ perfusion ratio by compressing blood vessels (Davies, 1999). In addition, TLV can mechanically remove debris and secretion from the airways (Galvin et al, 2013) and present surfactant-like and antiinflammatory properties (Zhu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%